Sustainability transition needs sustainable finance - Ryszawska, Bożena (Copernican Journal of Finance & Accounting, 2016)
Transition is a term used to describe conversion (evolution) from the existing model of economy and finance towards one based on increased social and environmental responsibility. The purpose of this study is to emphasise the role of sustainable finance in the sustainability transition process. The main thesis can be expressed as follows: the role of finance is changing from the dominant view rooted in neoclassical economic theory (to maximize profits, and shareholder wealth) towards one supporting sustainable development, green economy, low carbon economy also adaptation and mitigation of climate change. The article uses the multilevel perspective created by F.W. Geels effective in the analysis of the sustainability transition. Results of analysis: There is evidence that the old regime of finance destabilizes. Finances are slowly responding to new demand in sustainable economy to align with it.